The transition from arable lands to rubber tree plantations in northern Thailand impacts weed assemblages and soil physical properties. (31st July 2018) - Neyret, M.; Robain, H.; de Rouw, A.; Soulileuth, B.; Trisophon, K.; Jumpa, K.; Valentin, C.
Abstract: In South‐East Asia, rapid land use changes in recent decades have raised concerns for biodiversity and soil conservation. Weeds provide many ecosystemic services for soil protection and support biodiversity, and could mitigate the negative effects of intensification. We investigated the changes in weed assemblages and weed–soil interactions on a chronosequence from annual crops to mature rubber tree plantations. We sampled five fields for each of four land uses in mountainous northern Thailand (rainfed upland rice, maize, young rubber tree (RT) intercropped with maize, and mature RT). We characterized weed assemblages (abundance, richness) and soil properties (bulk density, water, carbon and nitrogen content). Rice had the most diverse and abundant weed assemblages. Weed assemblages differed between (i) rice, (ii) maize and young RT with maize and (iii) mature RT. Soil water content was the highest in mature RT. Other soil properties varied strongly within and among fields, and did not vary significantly among land uses. Water and nitrogen content increased overall with living soil cover but decreased with weed species richness in mature RT. Such interactions could provide a basis for sustainable weeding practices favourable to soil and biodiversity conservation.